2019
DOI: 10.1007/s13238-019-0647-7
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-resident memory-like ILCs: innate counterparts of TRM cells

Abstract: Innate lymphoid cells (ILCs) are defined as lymphocytes that lack RAG recombinase and do not express diverse antigen receptors; however, recent studies have revealed the adaptive features of ILCs. Mouse cytomegalovirus (MCMV)-and cytokine-induced memory natural killer (NK) cells circulate in the blood and are referred to as conventional memory NK cells. In contrast, virusand hapten-induced memory NK cells, hapten-induced memory ILC1s, and cytokine-induced memory-like ILC2s exhibit long-term residency in the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 98 publications
0
13
0
Order By: Relevance
“…NK cells are important for anti-tumor and anti-viral immunity, whereas ILCs may act to promote tissue repair (Ishizuka et al, 2016;Sun and Lanier, 2011). Although innate immune cells have classically been described as having a rapid, short-lived response, studies in the past decade have shown that the function of myeloid and innate lymphoid cells can be shaped and enhanced by prior antigenic exposure through epigenetic and metabolic changes or modulation of surface receptor expression (Netea et al, 2020;O'Sullivan et al, 2015;Rodriguez et al, 2019;Sun et al, 2009;Wang et al, 2020). The adaptive immune system is characterized by its diverse repertoire of antigen-specific receptors expressed by T and B lymphocytes and ability to retain immunological memory over decades.…”
Section: Introductionmentioning
confidence: 99%
“…NK cells are important for anti-tumor and anti-viral immunity, whereas ILCs may act to promote tissue repair (Ishizuka et al, 2016;Sun and Lanier, 2011). Although innate immune cells have classically been described as having a rapid, short-lived response, studies in the past decade have shown that the function of myeloid and innate lymphoid cells can be shaped and enhanced by prior antigenic exposure through epigenetic and metabolic changes or modulation of surface receptor expression (Netea et al, 2020;O'Sullivan et al, 2015;Rodriguez et al, 2019;Sun et al, 2009;Wang et al, 2020). The adaptive immune system is characterized by its diverse repertoire of antigen-specific receptors expressed by T and B lymphocytes and ability to retain immunological memory over decades.…”
Section: Introductionmentioning
confidence: 99%
“…ILCregs exist in the gut and control intestinal inflammation via the secretion of IL-10 [21] (Table 1). Tissue-resident memory ILCs exist in the liver or lung and have adaptive features, including virus and hapten-induced memory NK cells, hapten-induced memory ILC1s, and cytokine-induced memory ILC2s [22, 23]. Accumulating evidence also suggests that tissue-resident memory ILCs might represent the innate counterparts of resident memory T (T RM ) cells owing to some common features [22].…”
Section: Introductionmentioning
confidence: 99%
“…hILC2s, on the other hand, had the highest expression of activation receptors and exhaustion markers compared with other hILCs, suggesting that these cells were more chronically activated in bladder tumors compared with other hILCs ( p < 0.04) (Figure ; Table ). CD103 and CD69 were highly co‐expressed in hILC3s (Figure ), a characteristic of tissue‐resident innate memory cells, and non‐recirculating immune cells that reside in tumor sites 27,28 . ILC1s and ILC3s express lymphoid tissue‐homing receptors but can switch the expression of homing receptors to migrate to different tissue sites 29 .…”
Section: Resultsmentioning
confidence: 99%